Tindak Pidana Terorisme, Radikalisme dan Deradikalisasi di Indonesia - Yasmirah Mandasari Saragih; Zeno Eronu Zalukhu; Angga Sahputra Sirait; Zubaidah Zubaidah; Ansori Maulana (Pusat Riset dan Inovasi Nasional, 2025)
Terrorism is considered a crime against humanity and poses a serious threat to the sovereignty of states as it has an international scope and impact. This crime threatens global security and peace and undermines the welfare of society, thus requiring decisive and sustained eradication efforts to protect and respect human rights at large. radicalism reflects an attitude or view that is extreme and seeks social or political change in ways that are controversial or outside the norm. Perpetrators of terrorism often have radical views and choose violent acts as a way to achieve their goals. Prevention of terrorism through deradicalization is a proactive step and requires caution with consideration of the plurality of Indonesian society and the vulnerability of plurality to social conflict.